Collateralization of cerebellar output to functionally distinct brainstem areas. A retrograde, non-fluorescent tracing study in the rat - Ruigrok, Tom J.; Teune, Thea M. (Frontiers in Systems Neuroscience, 2014)
The organization of the cerebellum is characterized by a number of longitudinally organized connection patterns that consist of matching olivo-cortico-nuclear zones. These entities, referred to as modules, have been suggested to act as functional units. The various parts of the cerebellar nuclei constitute the output of these modules. We have studied to what extent divergent and convergent patterns in the output of the modules to four, functionally distinct brain areas can be recognized. Two retrograde tracers were injected in various combinations of the following nuclei: the red nucleus, as a main premotor nucleus; the prerubral area, as a main supplier of afferents to the inferior olive; the nucleus reticularis tegmenti pontis, as a main source of cerebellar mossy fibers; and the inferior olive, as the source of climbing fibers. For all six potential combinations three cases were examined. All 9 cases with combinations that involved the inferior olive did not, or hardly, resulted in double labeled neurons. In contrast, all other combinations resulted in at least 10% and up to 67% of double labeled neurons in cerebellar nuclear areas where both tracers were found. These results show that the cerebellar nuclear neurons that terminate within the studied areas represent basically two intermingled populations of projection cells. One population corresponds to the small nucleo-olivary neurons whereas the other consists of medium- to large-sized neurons which are likely to distribute their axons to several other areas. Despite some consistent differences between the output patterns of individual modules we propose that modular cerebellar output to premotor areas such as the red nucleus provides simultaneous feedback to both the mossy fiber and the climbing fiber system and acts in concert with a designated GABAergic nucleo-olivary circuit. These features seem to form a basic characteristic of cerebellar operation.